Achieving the competitive edge : - Jackson, Harry K. (John Wiley & Sons, 1996)
This book is a practical guide to improving business processes. It focuses on strengthening the company from the inside by defining all of the management tools available and analyzing the strengths and weaknesses of each in the light of today's business environment.